IMPROVING THE STUDENTSâ€™ SPEAKING SKILL THROUGH TALKING CHIPS (TC): A CLASSROOM ACTION RESEARCH ON SECOND SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM AT STAIN BENGKALIS - Rini Fitria (Politeknik Negeri Bengkalis, 2017)
Abstract: The objective of the research was to describe the learning atmosphere during the implementation of â€œTalking Chipsâ€ (TC) technique in Speaking skill. Besides, the research was also designed to know how the improvement of the studentsâ€™ Speaking skill during the implementation of â€œTalking Chipsâ€ (TC) technique. This research was a classroom action research. The research was carried out in second semester students of English Study Program at STAIN Bengkalis. This research was conducted in two cycles by following the procedure of action research, i.e. planning, implementing, observing, and reflecting. In collecting the data, the researcher used observation, interview, questionnaire, and test. The lecturer was the researcher assisted by collaborator as observer. The interview and questionnnaire were given to the students before and after the implementation of Talking Chips (TC). The tests were in the form of pre-test, post-test 1 and post-test 2. The data were analized qualitatively and quantitatively. The qualitative data were analized using Interactive Model of Data Analysis as propounded by Matthew M. Miles and A.M. Huberman. The results of the research showed that the learning atmosphere also improved. The class became more confident, fun and enjoyable. Furthermore, Talking Chips (TC) Technique was able to improve the studentsâ€™ Speaking Skill. It was proven by the increase of the studentsâ€™ mean score from 40.84 in pre-test to 45.92 in cycle 1, and 49.61 in cycle 2, although the results of the research were just a little bit improvement. It could be concluded that the use of Talking Chips has proven to be an effective way in teaching-learning of Speaking Skill on Second Semester of English Study Program at STAIN Bengkalis.Â Â Keyword: Speaking Skill, Talking Chips (TC) Technique